Patient-Rated Wrist Evaluation: Spanish Version and Evaluation of Its Psychometric Properties in Patients with Acute Distal Radius Fracture - Alfie, Veronica; Gallucci, Gerardo; Boretto, Jorge; Donndorff, Agustin; Dubois, Juieta Puig; Benitez, Sonia; Giunta, Diego; de Carli, Pablo (Journal of Wrist Surgery, 2017)
Purpose The purpose of this paper is to validate a Spanish version of patient-rated wrist evaluation (PRWE) and evaluate its psychometric attributes in a population of patients with distal radius fracture.Material and Methods A translation and cross-cultural adaptation of the PRWE to Spanish (PRWE-S) was performed according to standardized guidelines. A total of 50 patients with a distal radius fracture were included during the different steps of the study. The reliability of the new instrument was assessed in terms of construct validity with the Quick DASH (Disability of the Arm, Shoulder, and Hand). Internal consistency and test–retest stability were also examined.Results The Spearman's correlation test for analysis of the criterion validity (0.75) indicates a strong positive correlation between the PRWE-S and the Quick DASH. The internal consistency according to Cronbach's α was 0.96, and the intraclass correlation coefficient was moderate (0.46).Conclusion A Spanish version of the PRWE indicated good validity and reliability in distal radius fracture patients. This valuable tool can be used in Spanish-speaking countries to evaluate various aspects as pain and function in patients with injuries of the wrist.
Keywords: PRWE; translation; Spanish version; validity; reliability; distal radius fracture